Degradation of carbon-based materials under ablative conditions produced by a high enthalpy plasma jet - Gilberto Petraconi; Alexei Mikhailovich Essiptchouk; Leonid Ivanovich Charakhovski; Choyu Otani; Homero Santiago Maciel; Rodrigo Sávio Pessoa; Maria Luisa Gregori; Sônia Fonseca Costa (Journal of Aerospace Technology and Management, 2010)
A stationary experiment was performed to study the degradation of carbon-based materials by immersion in a plasma jet. In the experiment, graphite and C/C composite were chosen as the target materials, and the reactive plasma jet was generated by an air plasma torch. For macroscopic study of the material degradation, the sample’s mass losses were measured as function of the exposure time under various temperatures on the sample surface. A microscopic analysis was then carried out for the study of microscopic aspects of the erosion of material surface. These experiments showed that the mass loss per unit area is approximately proportional to the exposure time and strongly depends on the temperature of the material surface. The mass erosion rate of graphite was appreciably higher than the C/C composite. The ablation rate in the carbon matrix region in C/C composite was also noticeably higher than that in the fiber region. In addition, the latter varied according to the orientation of fibers relatively to the flow direction. These tests indicated an excellent ablation resistance of the C/C composite, thus being a reliable material for rocket nozzles and heat shielding elements of the protection systems of hypersonic apparatuses from aerodynamic heating.